Rough sets based spatial analysis for metal production area at mount nif - TUNCALI YAMAN, TUTKU (My University, 2022)
The Mount Nif (Olympus) Excavation has four excavation areas where southeast of Mount Nif, located in the east of Izmir, Turkey. A significant spot of the project is Karamattepe, defined as a metal production area in the Archaic Period, which is prominent with rich metal finds such as nearly 500 pieces of iron and bronze arrowheads, metal production furnaces, and slags. Albeit mentioned context seems suitable to spatial analysis, per contra, the area which has a natural incline in the north-south axis, had even been used as agricultural land for approximately 100 years in the modern period. As known, both natural slope and agricultural practices such as plowing and spudding in archaeological sites cause translocation, especially in small finds. Under these circumstances, the context does not seem suitable for spatial analysis with deterministic methods. The goal of the study is to understand the specs of the metal production area at Karamattepe by spatial analysis. Studied data include geolocations of arrowheads that are obtained from GIS, their Euclidean distances to the furnaces, various metrics (weight, length, i.e.), and analogical typology as inputs. With the proposed Rough Sets-based approach, the relations metal finds and production points was determined. It is thought that this study will shed light on the researchers to cope out multi-dimensional uncertainties for spatial analysis in landscape archaeology.

Nif (Olympos) Dağı Kazısı, İzmir’in doğusundaki Nif Dağı’nın güneydoğusunda yer alan dört farklı kazı alanına sahiptir. Projenin önemli bir sahası, Arkaik Dönem’e ait bir metal üretim alanı olarak tanımlanan ve 500’e yakın demir ve bronz ok ucu, metal üretim fırınları ve cüruf gibi zengin buluntularıyla öne çıkan Karamattepe’dir. Söz konusu bağlam her ne kadar mekânsal analize uygun görünse de aksine, kuzey-güney ekseninde doğal bir eğime sahip olan alan, modern dönemde yaklaşık 100 yıl boyunca tarım arazisi olarak bile kullanılmıştır. Bilindiği gibi hem doğal eğim hem de arkeolojik alanlarda gerçekleştirilen tarımsal uygulamalar özellikle küçük buluntuların yer değiştirmesine neden olmaktadır. Bu koşullar altında bağlam, deterministik yöntemler kullanılarak yapılacak mekansal analiz için uygun görünmemektedir. Bu çalışmanın amacı, Karamattepe’deki metal üretiminin özelliklerini mekansal bir analiz ile anlamaktır. Çalışılan veriler, CBS’den elde edilen ok uçlarının coğrafi konumlarını, alanda tespit edilen fırınlara Öklid mesafelerini, (ağırlık, uzunluk, v.b.) çeşitli metrikleri ve ok uçlarının analog tipolojisini içermektedir. Önerilen kaba küme teorisi temelli yaklaşımla metal buluntular ile üretim noktaları arasındaki ilişki belirlenmiştir. Bu çalışmanın, yerleşim arkeolojisinde mekansal analiz için çok boyutlu belirsizliklerin üstesinden gelmek için araştırmacılara ışık tutacağı düşünülmektedir.
Keywords: Rough Sets; Spatial Analysis; Metal Production; Arrowheads; Nif; Kaba Kümeler; Mekansal Analiz; Metal Üretimi; Ok Ucu